A Conversation with Judge Harry T. Edwards - Harry T. Edwards (Washington University Journal of Law & Policy, 2004)
On February 18, 2004, the Honorable Harry T. Edwards, Chief Judge Emeritus and Circuit Judge, United States Court of Appeals for the D.C. Circuit, delivered the 2004 Tyrrell Williams Lecture at Washington University School of Law in St. Louis. Rather than follow the usual lecture format, Judge Edwards participated in a “public forum.” He first answered questions sent to him by law students and members of the law school faculty in advance of his talk and then fielded inquiries from the audience. Most of the questions related to articles that Judge Edwards has written on collegiality in judicial decision making, judicial administration, social science models of decision making, interdisciplinary studies, the “harmless error” doctrine, legal education, and the legal profession. Judge Edwards’ answers to the questions raised at the public forum are reprinted below.
Keywords: Judicial process; Law – Study & amp; teaching